O impacto da burocracia nas pequenas e microempresas: uma análise do arcabouço legal - Silva, Pedro Henrique Fernandes (2013)
This work focuses on the problems faced by small and micro enterprises in the State of Rio de Janeiro, under the circumstances of an archaic and bureaucratic structure of the Brazilian state, which transforms the act of taking on a real adventure, as well as the challenges and risks the business itself, the bureaucracy eliminates most companies still in the early years of life . The segment focused on this work suffers , even more , the low capacity of mobilization and representation, not having, well, how to defend a state partner only success and never failure. The legislation itself acts as a barrier, with all rules decoupled from economic reality, establishing procedures that instead of being incentive become often insurmountable obstacles for small and micro enterprises. The tangle of laws creates a setting conducive to corruption , a direct consequence of the lack of objectivity and discretion of those with the function of legislating. Examples of laws shown throughout the text depict the true sangria health of these companies, as well as the amount of new Bills presented each year show that, unfortunately, we are still far from a change of direction. The paper aims to show some data through the damage to the state's economy because they are small and micro enterprises, contrary to what many think, the largest employers, is therefore of vital importance that their difficulties are treated as priority. Although, as stated, the State of Rio de Janeiro has served as an example of the current model, this situation is practically the same in all other units of the Federation, highlighting the importance of a general mobilization able to change the course of this story. However, it is also clear that this transformation involves a change of mindset, because without it, all wins will be punctual, no strength to build a new business scene.